Strengthening Local Wisdom-Based MSMEs through Production Optimization to Improve Local Economic Competitiveness - Raisa Fitri; Della Ayu Zonna Lia; Ita Prihatiningsih; Sudarmiatin Sudarmiatin (Institut Teknologi dan Bisnis Asia Malang, 2023)
Purpose: MSMEs are strategic businesses in driving the national economy, which are believed to be able to stabilize the financial system and economy because they have high economic resilience. Therefore, various supports are needed to improve the quality of MSME processed products, so the purpose of the community services is to help Alrosa MSME owners utilize technology to improve the quality of the products produced so that the products produced can be optimal and efficient. Method: The methods used are 1) identification, 2) implementation of activities, and 3) program evaluation. The activity was carried out at the production house of UMKM Alrosa Karangploso, Malang Regency. Practical Applications: The results of the community services are the increase in the quality and quantity of Alrosa MSME food products by utilizing spinner and oven technology and training in designing product packaging for MSMEs to make it attractive. Conclusion: The community services program provided to Alrosa MSMEs is well received and helpful in improving the quality of Alrosa MSME products.